Interactive Effects of Zinc-Arbuscular Mycorrhizal (AM) Fungi on Cadmium Uptake, Rubisco, Osmolyte Synthesis and Yield in Cajanus cajan (L.) Millsp. - Kaur, Harmanjit; Garg, Neera (International Journal of Sustainable Agricultural Research, 2020)
Cadmium (Cd) and Zinc (Zn) are two closely associated chemical elements having varied biological roles. Cd is a non-essential noxious element whereas Zn is an indispensable micronutrient at low concentrations but toxic to plants at higher levels. At the root surface, Cd competes with Zn for the same transmembrane carriers and Zn reduces Cd uptake in plants. Arbuscular mycorrhizal (AM) fungi are considered potential biotechnological approach for increasing plant tolerance to Cd-polluted soils. Applications of Zn and AM fungal inoculations might augment metal tolerance by reducing Cd uptake through their interactive effects. Thus, experiments were carried out to investigate the interplay between Zn (500 and 1000 mg kg-1 dry soil) and AM fungus [Funneliformis mosseae (T.H. Nicolson & Gerd.) C. Walker & A. Schüßler] on growth, nutrient management, photosynthetic efficiency, osmotic equilibrium and productivity in two pigeonpea (Cajanus cajan (L.) Millsp.) genotypes (Tolerant- Sel 85N and Sensitive- P792) exposed to Cd stress (25 and 50 mg kg-1 dry soil). Results revealed that accumulation of Cd and Zn individually reduced plant dry matter, total chlorophyll contents, Rubisco activity and nutrient uptake resulting in loss of yield, with Cd proving to be more toxic. However, Zn and AM reduced Cd uptake and their combined treatments enhanced plant biomass, photosynthetic ability and harvest index (HI) significantly by providing osmotic balance (total soluble sugars, free amino acids, proline, glycine betaine). The effects were more discernible in Sel 85N than P792 which could be directly correlated with its better ability for mycorrhizal colonization under stress.